Articular Lag Screw Fixation of a Proximal Humeral Fracture in a Dog - Holmberg, D. L. (Veterinary and Comparative Orthopaedics and Traumatology, 1997)
The use of screws placed from the articular surface in lag fashion for the repair of proximal femoral physeal fractures has been reported experimentally and clinically with mixed results. This report describes the use of the technique in the repair of a fractured proximal humeral physis.
Keywords: Humeral fracture; lag screw fixation; dog